Testing Steady-State Implications for the NAIRU - Gunnar Bardsen; Ragnar Nymoen (Norges Bank, 2000)
Estimates of the NAIRU are usually derived either from a Phillips curve or from a wage curve. This paper investigates the correspondence between the operational NAIRU-concepts and the steady state of a dynamic wage-price model. We derive the parameter restrictions that secure that correspondence. The full set of restrictions can be tested by econometric analysis of the wage-price system, and this method is demonstrated for Norwegian data. A set of necessary conditions can be tested from estimated wage curves alone. Existing international evidence from empirical wage equations are re-interpreted in light of these conditions.
hdl:11250/2500411
Keywords: C51; C52; E24; E31; J30; 330; NAIRU; Phillips curve; wage curve; steady state; natural rate; dynamic modelling